Generalized Brewster effect in dielectric metasurfaces - Ramón Paniagua-Domínguez; Ye Feng Yu; Andrey E. Miroshnichenko; Leonid A. Krivitsky; Yuan Hsing Fu; Vytautas Valuckas; Leonard Gonzaga; Yeow Teck Toh; Anthony Yew Seng Kay; Boris Luk’yanchuk; Arseniy I. Kuznetsov (Nature Communications, 2016)
Devices with greater freedom are desired in nanophotonics. Here, the authors demonstrate theoretically and experimentally that the generalized Brewster effect can be observed in an all-dielectric metasurface potentially for any angle, wavelength and polarization, due to electric and magnetic dipole interference.